New spirometry recommendations from the Brazilian Thoracic Association - 2024 update - André Luís Pereira de Albuquerque; Danilo C Berton; Eloara Vieira Machado Ferreira Álvares S Campos; Fernando José Pinho Queiroga-Júnior; Alfredo Nicodemos Cruz Santana; Bruno de Moraes Santos Wong; Diane Rezende Batista; Felipe Xavier de Melo; Fernando Moacyr Fragoso Didier-Neto; João Adriano de Barros; João Marcos Salge; José Alberto Neder; et al. (Jornal Brasileiro de Pneumologia)
ABSTRACT The latest pulmonary function guideline from the Brazilian Thoracic Association was published in 2002, since which there have been updates to international guidelines (mainly those from the European Respiratory Society and the American Thoracic Society), as well as new national and international publications on various aspects of the performance, interpretation, and clinical implications of spirometry. Despite those updates, a careful analysis of what applies to the reality in Brazil is essential, because there have been studies that evaluated individuals who are representative of our population and who could show responses different from those of individuals in other regions of the world. This document is the result of the work of a group of specialists in pulmonary function who evaluated relevant scientific articles that could be applicable to the population of Brazil. After the discussions, new spirometry guidelines were drawn up, covering various aspects such as its technical parameters and performance; its indications and contraindications; its interpretation; concepts of normality and their related variability; reference values; classification of functional severity; and response to an inhaled bronchodilator. Finally, the guidelines emphasize the need to always interpret spirometry results in the context of the clinical condition of the patient and of the pretest probability.